Comparison of airway dimensions in skeletal Class I malocclusion subjects with different vertical facial patterns - Ana Paula Flores-Blancas; Marcos J. Carruitero; Carlos Flores-Mir
ABSTRACT Objective: The aim of this study was to compare upper airway widths among skeletal Class I malocclusion subjects with different vertical facial patterns. Methods: The sample included a total of 99 lateral cephalograms of post pubertal individuals (18.19 ± 1.76 years old). The vertical facial pattern was determined by the Vert index. The McNamara method was used to quantify upper airway widths. ANOVA test and Student's t test for independent groups were used, when normal distribution was not supported Kruskal-Wallis test and U-Mann-Whitney test were used. A multiple linear regression analysis was also performed. Results: Statistically significant differences in several nasopharyngeal widths were found among the distinct vertical facial patterns. Subjects with brachyfacial pattern presented larger nasopharyngeal widths than subjects with mesofacial (p= 0.030) or dolichofacial (p= 0.034) patterns. The larger the Vert value, the larger the nasopharyngeal widths (R2= 26.2%, p< 0.001). At the level of oropharynx no statistically significant differences were found. Conclusion: It was concluded that nasopharyngeal linear anteroposterior widths in Class I malocclusion brachyfacial are larger than in mesofacial and dolichofacial individuals. The Vert index only explained 25% of the total variability. No correlation was found for the oropharyngeal widths.